CREATING RELIABLE AND RESILIENT GRAIN STORAGE FACILITIES IN THE FACE OF WAR AND THE GLOBAL FOOD CRISIS (Collection of scientific works «Modern structures of metal and wood», 2024)
The  article  describes  in  detail  the  complete  engineering  methodology  for  the verification  calculation  of  steel  grain  storage  structures  based  on  the  pan-European  Eurocode standardisation system in accordance with the provisions of DBN B.2.6-221:2021 and DSTU-N B EN  1991-4.  The  emphasis  of  the  work  is  on  determining  the  mechanisms  for  regulating  the reliability of grain storage structures within the framework of the application of semi-probabilistic calculation  in  the  form  of  the  limit  state  method.  To  assess  the  stress-strain  state  of  individual structural elements of the silo, two methods were used: the direct method of finite element analysis without taking into account the effects of geometric and physical nonlinearity and the theoretical method  based  on  the  membrane  theory  in  a  linear-elastic  formulation  assuming  linear-elastic material characteristics and the linear theory of small deformations. The practical implementation of the methodology was tested on the example of real steel silo structures. It is established that the change in the level of reliability of steel grain storage structures within the framework of the limit state  method  is  carried  out  through  a  system  of  partial  coefficients  that  take  into  account  the stochastic  properties  of  external  influences,  variability  of  material  characteristics,  types  of calculations,  the  degree  of  importance  of  structural  elements  in  the  structure  and  the  degree  of responsibility  of  the  silo  as  part  of  the  enterprise.  The  specified  values  of  the  partial  reliability factors  are  governed  exclusively  by  the  regulatory  requirements  and  guidelines  of  the  national annex and cannot be adjusted by the design specification. The given values of the coefficients are limited  to  limit  state  checks  on  the  bearing  capacity  and  serviceability  of  structures  under  static load, including cases where the dynamic impact is assessed using equivalent quasi-static loads with appropriate amplification factors.